Evaluation of Singapore Airlines' inflight service quality using the SERVQUAL model. - Lee, Jeffery Peng Soon. (2008)
The study will first attempt to derive a measurement index for SIA inflight service quality. It will also investigate the differences in passengers’ expectation of inflight service quality for various categories of passengers (for example: travel classes, length of flight, nationality). To complete the evaluation, the study would seek to identify SIA inflight service quality problems, examine their causes and suggest means to solve them.